Desa Wisata Umbul Udal-udalan Go Digital: Pelatihan Manfaat Media Digital untuk Masyarakat - kharisman, Prasiwi Citra Resmi; Maharani Ayuning Tyas (Jurnal Abdimas Pariwisata, 2025)
Umbul Udal-Udalan is a water-based tourism destination in Ngudal Hamlet, Nglebak Village, Tawangmangu District, Karanganyar Regency. This destination is part of the Nglebak Tourism Village area and possesses significant tourism potential that has yet to be fully realised, particularly in promotional strategies. To support the development of this tourism village, a community outreach initiative was carried out focusing on the utilisation of digital media as a strategic promotional tool. The primary objective of this activity was to enhance the capacity of tourism village managers and the surrounding community in leveraging digital platforms to promote local tourism assets. Specifically, the initiative emphasised the optimisation of Google My Business (GMB) and the Instagram social media platform. The method employed in this program involved the delivery of informative material and interactive engagement through focused group discussions. The results of the activity demonstrated an increased understanding among participants regarding the vital role of digital media in tourism promotion. This outreach initiative is expected to contribute to an increase in tourist visits and foster local economic development in Umbul Udal-Udalan. In conclusion, by providing training on the use of mass media, the local community is encouraged to cultivate awareness of sustainable tourism village management practices that yield positive outcomes for the broader society.